2015
DOI: 10.3926/jiem.1652
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of social media channel preference for student engagement improvement in universities using entropy and TOPSIS method

Abstract: Abstract:Purpose: To analyze students' social media preference in order to improve student engagement with university by examining social media implementation quality in terms of information and service quality.Design/methodology/approach: Research methodology is started with the hierarchy creation of student engagement with university which then translated into questionnaire. This questionnaire was distributed to 58 universities in Jakarta (Indonesia's capital). The questionnaire result was analyzed with entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…The research involved a survey of 58 universities in Jakarta. In this case, it reflects the formulated business model as a result (Meyliana, 2015;Meyliana, Hidayanto, & Budiardjo, 2015). The researchers applied the BPM model as the foundation for university blockchain.…”
Section: Business Process Model For Universitymentioning
confidence: 94%
“…The research involved a survey of 58 universities in Jakarta. In this case, it reflects the formulated business model as a result (Meyliana, 2015;Meyliana, Hidayanto, & Budiardjo, 2015). The researchers applied the BPM model as the foundation for university blockchain.…”
Section: Business Process Model For Universitymentioning
confidence: 94%
“…The research indicated that in-person courses elicit higher levels of engagement than online classes (Burch, et al, 2016). Though inperson classes are the ideal design in terms of engagement, better utilization of online mediums, such as YouTube and podcasts, would likely have a positive effect of engagement as well (Meyliana, et al, 2015). Thus, the potential of improving the design of the course to increase completion rates is an interesting topic that we have continued to explore.…”
Section: Literature Review: Analysis and Synthesis Of Articles Selectedmentioning
confidence: 98%
“…In the study by Meyliana et al [11], students' social media preference was analysed to increase student engagement with the university. Data was collected from 1021 students from fifty-eight Indonesian universities using questionnaires [11,12]. Entropy was used to process data and assign criteria weights for social media preference.…”
Section: Related Workmentioning
confidence: 99%
“…Using the TOPSIS (Technique for Order Preference by Similarity to the Ideal Solution) method, it was established that the implementation of social media was more dependent on information quality as opposed to service quality. However, while comprehensiveness and usefulness of information were highly essential to students, they also valued system availability, efficiency, and fulfilment as they directly impacted their expectation and active learning process [11,12].…”
Section: Related Workmentioning
confidence: 99%